PENGARUH KOMITE AUDIT INTERNAL PADA LAPORAN BERKELANJUTAN (ESG) DI PERUSAHAAN YANG TERDAFTAR PADA BEI - Feyza Putri , Alivia Riski; Putikadea, Insyirah (LPPM Universitas Bina Bangsa, 2025)
This study aims to analyze the influence of the internal audit committee on the disclosure of Environmental, Social, and Governance (ESG) sustainability reports in companies listed on the Indonesia Stock Exchange (IDX) for the period 2021–2023. The independent variables studied include the independence of the audit committee, the number of audit committee meetings, and the size of the audit committee, while ESG disclosure as the dependent variable is measured based on sustainability indicators in accordance with the Global Reporting Initiative (GRI) standards. The research method used is a quantitative method using a sample of 25 companies in the Leader Index. Data analysis was carried out using multiple linear regression techniques to measure the influence of these variables on ESG Disclosure. The results of the study show that the three independent variables, namely the independence of the audit committee, the number of audit committee meetings, and the size of the audit committee, have a positive and significant effect on ESG disclosure. For investors, these results can be a consideration in evaluating corporate governance related to sustainability before making investment decisions. Meanwhile, policy makers can use these findings to formulate regulations that encourage better ESG governance, thereby supporting long-term sustainability in the business sector.